Implementasi Manajemen POAC pada Ekstrakurikuler Pendidikan Kepramukaan dalam Meningkatkan Prestasi Nonakademik Siswa di MAS Muhammadiyah Songing: POAC-Based Managerial Governance of the Scouting Extracurricular Program in Fostering Student Achievement at MAS Muhammadiyah Songing - Muallim Muallim (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2026)
The rising phenomenon of moral degradation and the fading of ethics among today’s youth demand a more structured management of student activities as an instrument for character building. This study aims to analyze the implementation of POAC management in Scout extracurricular activities at MAS Muhammadiyah Songing Sinjai to improve non-academic achievement. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The results indicate that management functions are operating effectively: (1) Planning is conducted participatorily based on performance evaluation and tiered recruitment; (2) Organizing applies task specialization according to the General Proficiency Requirements (SKU) and ad-hoc work teams; (3) Actuating focuses on joyful learning methods and time discipline, which impact character internalization; and (4) Controlling utilizes a standardized, multi-layered evaluation system (incidental, monthly, and annual). The study concludes that structured, disciplined, and measurable managerial governance is the key factor in maintaining consistent student achievement.